The Geometry of Selecting of Iranian Heroes by Iranian Teenagers - Jafari, Mostafa; Vaezizadeh, Zahra (Advances in Social Sciences Research Journal, 2017)
Marketing idea investigate thoughts and view of people in the society until reach choosing particular products based on thoughts of consumers that it can forecast the future needs and meet it with adequate response.In this marketing producers encourage people to accept their thoughts that they could keep their way in the target market. One of this marketing tools are advertising and media. The media can have a great impact on public opinion that it affects on consumer buying behavior. And even sometimes people unconsciously absorbed through the products that they propaganda in the media. In this article discusses the reasons for the rejection of Iranian heroes by the Iranian teenagers that one of the reasons can be revers acting producers and media programs. Methodology:In this study questionnaires set with qualitative questions and includes tow parts, one part for parents and the other part for teenager that were completed and returned by them. Using by snowball method 400 questionnaire were distributed that 205 questionnaire from teenager and 95 questionnaire from parents were collected. Results :Finally , we analyzed the influence of media, attractiveness of the products, family and tendency of accept the foreign culture Key words : Myth , hero, marketing idea, shopping behavior